Study of precision forging technology for complicated high strength aluminum alloy part - Junwei Cheng; Xianzhang Feng; Li Sizhong; Guo Xiaoqin; Xia Juchen (Functional Materials, 2017)
In order to investigate forging feasible of SC100-T6 high silicon aluminum alloy, its plastic deformation behavior during high temperature was studied by isothermal compression of cylindrical specimens using Gleeble-1500. The experiment was carried out over of deformation temperature form 390C to 490C, strain rate form 0.006s⁻¹ to 0.036s⁻¹. The result showed that the alloy had some plastic at high temperature, its flow stress was controlled by both strain rate and deformation temperature, which the flow stress decreases with the increase of temperature, while increases with the increase of strain rate. In order to prove alloy die formation, the die forming process with small flash for a complicated Al-alloy part was studied with theoretical analysis and experiment methods. Two steps die forming process was laid down, in which pre forming step the metal was distributed in accordance with the forging. Then in final step, the die cavity was filled easily with larger force. At last, the right heating process of material and die, the experiment was carried out at 800T hydraulic press successfully, and the qualified forge piece was obtained. The microscopic structure of raw material and forging material was investigated, the result showed that few Si blocks in raw material were broken small grain and structure was homogenized and improved to some extent, which improved the comprehensive mechanical property of the part to some extent.